The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/ejss.13240
|View full text |Cite
|
Sign up to set email alerts
|

Soil fungal and bacterial communities are altered by the incorporation of leaf litter containing a fungal endophyte

Abstract: Litter decomposition plays a key role in nutrient cycling across ecosystems. The presence of Epichloë endophytes in grass plants affects litter decomposition. The overall effects of leaf litter containing Epichloë endophytes on the chemical and biological properties in non-rhizosphere soils have not previously been examined.The current study is aimed to understand the effect of direct incorporation of leaf litter from Epichloë endophyte-infected perennial ryegrass (Lolium perenne) on soil chemical characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 116 publications
(147 reference statements)
0
2
0
Order By: Relevance
“…Soil microbial diversity is influenced by both upward (bottom-up) and downward (top-down) factors, such as resources and consumers [110][111][112][113]. In this study, the effects of plant diversity were found to be relatively insignificant (Figure 5).…”
Section: Stepwise Action Of Multiple Trophic Levels Ultimately Drives...mentioning
confidence: 59%
“…Soil microbial diversity is influenced by both upward (bottom-up) and downward (top-down) factors, such as resources and consumers [110][111][112][113]. In this study, the effects of plant diversity were found to be relatively insignificant (Figure 5).…”
Section: Stepwise Action Of Multiple Trophic Levels Ultimately Drives...mentioning
confidence: 59%
“…In leaf litter–soil ecosystems, nutrient release from leaf litter is a soil-microbe-mediated decomposition process in which soil microbial communities secrete various enzymes that mineralize complex organic matter into small molecules that are easily absorbed by plants [ 6 , 7 ]. At the same time, leaf litter provides abundant energy and nutrient inputs for microbial growth and reproduction, and participates in their metabolic processes, thus, influencing the abundance and diversity of soil microorganisms [ 8 , 9 ]. The effects of leaf litter on soil microorganisms are inconsistent among different tree species due to the variability in composition and secondary metabolites [ 10 ].…”
Section: Introductionmentioning
confidence: 99%